The Architecture of Wind: Microclimatic Strategies in Roman Villae Maritimae across the Mediterranean (Case Studies from Tripolitania) - Concetta Cataldo (European Scientific Journal, ESJ, 2025)
This study examines four maritime villas located in the Tripoli area, aiming to highlight how Roman domestic architecture adapted spatially to local climatic conditions. In particular, it hypothesises that the combination of porticus and cryptoporticus formed an architectural device conceived to exploit the natural direction of the winds in order to ensure the passive cooling of residential spaces. Such interpretations, especially concerning the Tripolitanian villas, were partially advanced by mid-twentieth-century scholars. However, they have never been systematically organised within a comparative, interprovincial framework. The data employed in this study derive from a doctoral project that analyses, through published cartography and relevant scientific literature, the architectural evidence of maritime villas along the coasts of the Roman Mediterranean provinces, with the aim of identifying common architectural typologies. Preliminary findings indicate that these strategies of environmental architecture may represent a regional peculiarity of Tripolitania, rather than a broader pattern within the Roman world.